2016
DOI: 10.1111/jvh.12571
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C genotype distribution in patient and blood donor samples in South Africa for the period 2008–2012

Abstract: There are limited molecular epidemiological studies of hepatitis C at a national level in South Africa. The introduction of newer treatment modalities for hepatitis C requires knowledge of the genotypes as these may have different prognostic and therapeutic implications. This retrospective study describes genotype distributions of patients attending specialist clinics and a blood donor group studied during the period 2008-2012 in South Africa. Residual samples from diagnostic viral load testing from specialist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
(82 reference statements)
3
15
0
Order By: Relevance
“…The circulating prevalence of HCV genotypes 1a and 3a is similar to other countries where HCV infection is networked and predominantly spread through the sharing of contaminated injecting equipment among PWID [43,44]. However, of note in South Africa, genotype 5a (a unique and prevalent genotype [45]) was not found and this suggests that 5a circulates in the general population and not in PWUD/ID or other KPs.…”
Section: Hcv Prevalencesupporting
confidence: 51%
See 1 more Smart Citation
“…The circulating prevalence of HCV genotypes 1a and 3a is similar to other countries where HCV infection is networked and predominantly spread through the sharing of contaminated injecting equipment among PWID [43,44]. However, of note in South Africa, genotype 5a (a unique and prevalent genotype [45]) was not found and this suggests that 5a circulates in the general population and not in PWUD/ID or other KPs.…”
Section: Hcv Prevalencesupporting
confidence: 51%
“…The overall HBsAg prevalence of 4% is similar to the general population [45,9]. This may seem somewhat surprising given that we would expect these high risk groups to show a higher prevalence than that of the general population.…”
Section: Hbvmentioning
confidence: 77%
“…6 An analysis of blood donors and the general population in South Africa showed that overall GT5 was a prevalent genotype and accounted for 54% of HCV infections in Black South Africans. 7 HCV GT5 has also been reported in some regions of Belgium, France, Spain, Greece, the Netherlands, Luxembourg and Syria. [8][9][10][11][12][13] These unusual pockets of GT5 infection in Europe are among individuals who have not travelled.…”
Section: Hcv Genotype 4-5-6 Epidemiology Hcv Genotypementioning
confidence: 92%
“…However genotype 5a (a unique and prevalent genotype) was not found. A study of blood samples from patients attending specialist clinics (n=941) and blood donors (n=294 ) between 2008 and 2012 identi ed genotype 5a to be common among specialist clinic patients (36%) and particularly common (60%) among people over 50 years old in both groups, and among Black African people (54%) [56]. The lack of genotype 5a in this study suggests that the modes of transmission of identi ed genotypes among PWUD/ID and other KPs differs from older patients attending specialist clinics, some of whom contracted HCV through blood transfusions and unsafe medical injections [57], traditional practices such as tribal scari cation [58] or unknown risks.…”
Section: Hcv Prevalencementioning
confidence: 99%